Pengaruh Risiko, Tingkat Efisiensi dan Good Corporate Governance terhadap Kinerja Keuangan pada Bank Umum yang Terdaftar di Bursa Efek Indonesia Periode 2014-2018 - Rahmawati Fitriana; Dzikri Isgifiernanda (Jurnal EKSIS, 2022)
This study aims to determine the effect of Return On Investment (ROI) on CAR, the influence of Operating Income Operating Costs (BOPO) on CAR, the influence of Net Interest Margin (NIM) on CAR, the effect of Net Interest Margin (NIM) on CAR, influence of Loan to Deposit Ratio (LDR) on CAR, and the effect of Good Corporate Governance (GCG) self assessment of CAR simultaneously on commercial banks listed on the Indonesia Stock Exchange (IDX) in the period 2014 - 2018. The data used in this study are secondary data in the form of annual financial ratios with 35 observations. Data collection was obtained through the official website of the Indonesia Stock Exchange in the 2014-2018 period. Sampling was done by purposive sampling with a total of 7 banks. The results showed ROI had non significant effect on CAR. BOPO has non significant effect on CAR. NPL has non significant effect on CAR. NIM has a significant effect on CAR. LDR has non significant effect on CAR. GCG has non significant effect on CAR.